Infections after spine instrumentation: effectiveness of short antibiotic treatment in a large multicentre cohort. (26th January 2021) - Benavent, Eva; Rodríguez-Pardo, Dolors; Ulldemolins, Marta; Sobrino-Diaz, Beatriz; Bustinduy, María Jesús; Escudero-Sanchez, Rosa; Nodar, Andrés; Sorli, Luisa; Del Toro López, María Dolores; Bahamonde, Alberto; Vilchez, Helem H; Duran, Joan; et al.
Abstract: Background and objectives: Available information about infection after spine instrumentation (IASI) and its management are scarce. We aimed to analyse DAIR (debridement, antibiotics and implant retention) prognosis and evaluate effectiveness of short antibiotic courses on early forms. Methods: Multicentre retrospective study of patients with IASI managed surgically (January 2010–December 2016). Risk factors for failure were analysed by multivariate Cox regression and differences between short and long antibiotic treatment were evaluated with a propensity score-matched analysis. Results: Of the 411 IASI cases, 300 (73%) presented in the first month after surgery, 48 in the second month, 22 in the third and 41 thereafter. Infections within the first 2 months (early cases) occurred mainly to older patients, with local inflammatory signs and predominance of Enterobacteriaceae, unlike those in the later periods. When managed with DAIR, prognosis of early cases was better than later ones (failure rate 10.4% versus 26.1%, respectively; P  =   0.02). Risk factors for DAIR failure in early cases were female sex, Charlson Score, large fusions (>6 levels) and polymicrobial infections (adjusted HRs of 2.4, 1.3, 2.6 and 2.26, respectively). Propensity score matching proved shorter courses of antibiotics (4–6 weeks) as effective as longer courses (failure rates 11.4% and 10.5%, respectively; P  =   0.870). Conclusions: IASIs within the first 2 months could be managed effectively with DAIR and shorter antibiotic courses. Clinicians should be cautious when faced with patients with comorbidities, large fusions and/or polymicrobial infections.